Development of an Analgesic Cream Formula - Termtanasombat, Pranee (Journal of Health Science of Thailand, 1992)
This study aimed to develop a formula of analgesic cream, a popular medicine for the alleviation of ache and pain. The main target was to obtain a stable and readily absorbable preparation. Physicochemical and action - ingradient releasing property of three different formula were compared. It was found that the most appropriate formula was made up of 1.20% carbopol 940 and 4.0% lauryl sulfate as emulsifier. The active ingradients of the formula were 15.0% methyl salicylate, 1.25% eugenal, 6.0% Menthol and 2.0% Camphor. This formula was highly appropriate because of its stability, goof absorption, non-greasiness when applied to the skin, case to apply and good dispersionover the skin. As a result, a good quality preparation was obtained at a very cheap price.